Binary crossroads: decoding the dual nature of digital tools in higher education - França, Marcela (2024)
Digital transformation has become a pivotal topic across diverse industries lately, with education taking a prominent position. Commencing in the 1980s and gaining importance in the 1990s with the advent of personal computers and the internet (Kraus et al., 2021), it was the COVID-19 pandemic that exponentially accelerated this process (Rodríguez-Abita & Bribiesca-Correa, 2021). Consequently, digital technologies emerged as the quintessential means for the continuity of social and economic activities worldwide (Perkin & Abraham, 2021). However, as highlighted in the 2023 Global Education Monitoring Report on technology in education (UNESCO, 2023) the inclination to perceive digital technologies as universally applicable tools, suitable for any situation unravels three inherent paradoxes within the realm of education. The first one revolves around the notion that digital technologies could supplant educators, driven by the allure of personalized learning. Rather than being viewed as substitutes, they should be seen as complementary entities. The second paradox centers on the belief in effortless access to technology and its potential to enhance learning effectiveness, juxtaposed with its role in exacerbating educational disparities. Although digital technologies have become increasingly affordable over time, universal accessibility to both devices and the internet remains an elusive goal. During the pandemic, low-income students worldwide faced inadequate access to remote learning. The third paradox arises from the dichotomy between the endeavor to establish education as a global common good and the recognition that commercial and private interests invariably intersect with educational data. Consequently, only a select few countries legally guarantee the privacy of students’ data. Given these circumstances, investments in Cybersecurity within HEIs are of paramount importance. They manage a substantial volume of confidential information, including students’ grades, fees, research, and personal data. Therefore, safeguarding these records should be accorded high priority (Varma et al., 2021). Additionally, other paradoxes can be noticed in this context. Conventional wisdom often presupposes professors are digitally illiterate whilst young people called digital natives can leverage the use of digital technologies. That statement may not be universally applicable. According to Day Good (2021), professors in Europe and the US have integrated new media into classrooms to engender more engagement since 1910, while some young students display a relative unfamiliarity with their pedagogical application (Rodríguez-Abitia e Bribiesca-Correa, 2021). Despite digital tools' effectiveness in self-learning, “Zoom fatigue” has become a phenomenon among students (Carțiș, 2023). Thus, the relevance of this study is to understand and discuss the ambivalence of digital technologies in the teaching and learning processes in higher education. Most studies advocate for how digital tools can facilitate assessment in education (Díaz-Garcia, 2023; Haleem et al., 2022; Mohamed Hashim et al., 2021; Varma et al., 2021), whereas some shed light on a growing inequality of educational opportunities when dealing with digital technologies (Pashkov and Pashkova, 2022; Schia & Gjesvik, 2020) and just a few bring these two different perspectives together in the same investigation. Due to several pros and cons, this study underscores the ambivalence of using digital technologies in the teaching and learning processes in higher education in Portugal. It aims to understand the positive and the negative aspects of digital tools in this context. To accomplish this objective, the study will be theoretically underpinned by the New Media theory, which encompasses the internet, and the media related to the digital age and its new way of communication. For the empirical study, a qualitative methodology within an interpretive paradigm will be employed. This will involve conducting semi-structured interviews, either in person or via video communication platforms such as Zoom. Given the exploratory nature of this study, the number of participants will be limited to ten students from the Lisbon metropolitan area, which represents the highest population density in Portugal. Hence, it’s imperative to acknowledge that this study is delimited in its scope, as it does not encompass professors or digital leadership teams responsible for implementing digital transformation initiatives and conducting staff training in HEIs. This aspect will be addressed in the ongoing research within the doctoral program. A suggestion for future research would be a broader study involving younger students from the Global South, who face digital access barriers and can’t pursue higher education due to financial constraints. So, there is a vast environment to inquire about the benefits and drawbacks of using technology in education.